2023
DOI: 10.1111/1753-0407.13436
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health literacy interventions on glycemic control and self‐management outcomes among type 2 diabetes mellitus: A systematic review

Jamila Butayeva,
Zubair Ahmed Ratan,
Sue Downie
et al.

Abstract: Diabetes imposes an increasing health and economic burden on individuals living with it and their societies worldwide. Glycemic control is necessary to reduce morbidity and mortality of type 2 diabetes mellitus (T2DM). Self‐management is the primary tool for managing diabetes. Health literacy (HL) is the primary driver of self‐management activities. The aim of this review is to evaluate the impact of HL interventions on glycemic control and self‐management outcomes among T2DM. MEDLINE, CINAHL, PubMed, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…This fact is consistent with the results of a recent systematic review showing that health promotion interventions are positively correlated with the increased of knowledge and also controlling the glycemic level. This could be explained by the fact that nurses tend to be able to understand the cirsumstances, linguistic, and socioeconomic backgrounds with patients in order to provide interventions [9]. A study by Ramadhani et al (2019) shown that the more effective the self-care, the lower the HbA1c and the fasting blood glucose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact is consistent with the results of a recent systematic review showing that health promotion interventions are positively correlated with the increased of knowledge and also controlling the glycemic level. This could be explained by the fact that nurses tend to be able to understand the cirsumstances, linguistic, and socioeconomic backgrounds with patients in order to provide interventions [9]. A study by Ramadhani et al (2019) shown that the more effective the self-care, the lower the HbA1c and the fasting blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…03 2023 ISSN. 2808-4608 a relationship between BMI and HbA1c, patient with higher BMI tend to have higher HbA1c levels [9]. Self-care management is an essential tool for patient with diabetes to manage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes patients with lower health literacy, due to limited reading and mathematical abilities, are more likely to have suboptimal blood sugar control and an increased risk of diabetes complications (9). Conversely, a higher level of health literacy can effectively control blood sugar levels, manage complications, and enhance quality of life for diabetes patients (10). The level of health literacy may vary among different diabetes patients based on factors such as cognitive level and treatment stage (11).…”
Section: Introductionmentioning
confidence: 99%